Simulation-supported maintenance design and decision-making using agent-based modeling technology. Issue 1 (2021) - Kono, T.; Haneda, K.
Abstract: The optimization and continuous update of maintenance design, such as organization plans or introducing Internet-of-Things, are crucial for reliable and profitable maintenance business. However, various factors and interactions in maintenance make quantitative estimations of risk difficult and slows the improvement process. We developed a maintenance-business simulator on the basis of agent-based modeling that is applicable to a wide range of industries for testing various types of improvements. We applied our simulator to an organization plan of a medical-equipment business. We determined future business risks and tested the mitigation plan with the simulator.